Ingen vei utenom Arkeologiske undersøkelser i forbindelse med etablering av ny rv. 3/25 i Løten og Elverum kommuner, Innlandet - Løchsen Rødsrud, Christian (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"In 2015, the Museum of Cultural History at the University of Oslo carried out excavations in Løten and Elverum municipalities, Innlandet County. Al together, 79 cultural heritage sites, spanning in date from the Neolithic to the Middle Ages were excavated, including a site with burial cairns a Skillingstad, iron furnaces at Ånestad, trapping pits for elk, charcoal pits, cooking pit sites and the remains of several prehistoric fields. In addition, the book offers excavation results from adjacent areas, including a smithy from Hedmarken and a rich blacksmiths hoard from Østerdalen. A selection of articles give detailed presentations of the most important sites, while the results are put into a broad, cultural-historical context in the remaining articles. The excavations and subsequent work has generated new and central knowledge that illuminates the prehistory of southeastern Norway, but which also has relevance far beyond the region's borders. The project has provided a unique opportunity to shed light on how farms and outfield resources were integrated in the Iron Age. At the same time, the project work highlighted Løtens and Elverum's strategic location for the traffic between Østerdalen and Hedmarken - there was no other way between these two regions. "